PENGARUH KUALITAS PELAYANAN DAN KEDISIPLINAN PEGAWAI TERHADAP KEPUASAN NASABAH BANK BTPN SYARIAH - Mardianti, Artie; Hasna Nabila, Ajeng (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2021)
Sharia national pension savings bank (BTPNS) is a company that provides financial products and services to people who are mengarh or pre-prosperous. Therefore, it is very necessary that BTPNS will foster discipline and provide the best service class for employees in their performance for underprivileged people. The purpose of this study is to understand whether employee discipline and service have a major impact on customer satisfaction levels. In this study, using a quantitative method with a research population of 2022 people who became BTPNS customers in the Cisarua area, Bogor Regency, with a sample of 100 customers. The results of the observation stated that the level of service and discipline had a very positive and relevant impact on customer satisfaction. This is confirmed from the results of hypothesis testing which states the relevant numbers of the two independent variables that help the hypothesis.